Focus: Oxygen isotope microanalysis across incremental layers of human bone: Exploring archaeological reconstruction of short term mobility and seasonal climate change. (November 2019) - Maggiano, Corey M.; White, Christine D.; Stern, Richard A.; Peralta, J. Salvador; Longstaffe, Fred J.
Abstract: In archaeological populations the oxygen isotope composition ( δ 18 O) of human bones and teeth can be used to reconstruct climatic conditions and landscape mobility by serving as a proxy for changes in δ 18 O of consumed water. Until now, providing this information at the seasonal scale, across broad periods of an individual's life, has been considered impossible because bone remodeling was thought to completely disrupt meaningful patterns preserved in bone microstructure. Recent studies, however, have described large (often > 1 mm) deposits of incremental primary bone persisting well into adulthood, and new technology permits finer scale analysis than ever before. Our objective was to determine the δ 18 O variation across human primary bone layers using high spatial resolution Secondary Ion Mass Spectrometry (SIMS). Results show patterned sinusoidal periodicity, similar to expectations for weather-induced fluctuations in seasonal drinking water. The bone formation rate suggested by the isotopic variation in our study is consistent with other histological assessments of primary lamellar bone formation. The technique thus enables sampling of δ 18 O at approximately monthly intervals over more than a decade of bone deposition. Because bone is the most commonly recovered archaeological tissue, applications of this method, even using fragmentary remains, have the potential to enable more detailed reconstructions of political, economic, health, and sociocultural change at life history levels. Future applications may also include identification of remains in historic and forensic contexts and determination of developmental or pathogenic rates in ancient or modern health investigations. Graphical abstract: Image 1 Highlights: Secondary Ion Mass Spectrometry reveals monthly oxygen isotope variation in human bone. Sinusoidal changes in oxygen isotopes suggests weather induced seasonality in drinking water. Suggested bone growth rate (~0.75  μ m/day) fits expectations and prior reports.